Population development and breeding success of Dark-bellied Brent Geese Branta b. bernicla from 1991–2011 - Ebbinge, Bart S.; Blew, Jan; Clausen, Preben; Günther, Klaus; Hall, Colette; Holt, Chas; Koffijberg, Kees; Le Dréan-Quénec’hdu, Sophie; Mahéo, Roger; Pihl, Stefan (Wildfowl, 2013)
The Dark-bellied Brent Goose Branta bernicla bernicla is the largest of the six Brent Goose populations, which collectively number around 600,000 birds globally. After a major decline to 16,500 geese in 1958, numbers recovered during the 1970s and 1980s to a peak of c. 330,000 individuals between 1992 and 1994. From 1994 onwards the population declined again to 200,000–250,000. This decline has been attributed to poor breeding, associated with faltering cycles of Siberian Brown Lemming Lemmus sibiricus (predominantly) and Palearctic Collared Lemming Dicrostonyx torquatus abundance on the breeding grounds on the Taimyr Peninsula, where lemmings are a main food resource for potential predators of goslings. Darkbellied Brent Geese only breed well in peak lemming years (Summers & Underhill 1991), and this usually occurs every three years, but the frequent failure since 1994 of lemming numbers to peak (except in 2005) has resulted in the absence of very good breeding years for the geese (Nolet et al. 2013). The mid-winter distribution has shown a marked shift towards France over the last decade. France currently supports 50% of the population in January, Great Britain 35–40%, the Netherlands 15–20%, and Germany and Denmark 2%. In spring, almost the entire population gathers in the Wadden Sea, leaving only 4% of the population in Great Britain, and virtually none in France, with the Dutch part of the Wadden Sea supporting 40–45%, the German section 45–50% and Denmark 6%.